Rectal swab screening assays of public health importance in molecular diagnostics: Sample adequacy control. Issue 2 (March 2018) - Glisovic, Sanja; Eintracht, Shaun; Longtin, Yves; Oughton, Matthew; Brukner, Ivan
Abstract: Rectal swabs are routinely used by public health authorities to screen for multi-drug resistant enteric bacteria including vancomycin-resistant enterococci (VRE) and carbapenem-resistant enterobacteriaceae (CRE). Screening sensitivity can be influenced by the quality of the swabbing, whether performed by the patient (self-swabbing) or a healthcare practitioner. One common exclusion criterion for rectal swabs is absence of "visible soiling" from fecal matter. In our institution, this criterion excludes almost 10% of rectal swabs received in the microbiology laboratory. Furthermore, over 30% of patients in whom rectal swabs are cancelled will not be re-screened within the next 48 h, resulting in delays in removing infection prevention measures. We describe two quantitative polymerase chain reaction (qPCR)-based assays, human RNAse P and eubacterial 16S rDNA, which might serve as suitable controls for sampling adequacy. However, lower amounts of amplifiable human DNA make the 16s rDNA assay a better candidate for sample adequacy control.